2022
DOI: 10.1155/2022/7012889
|View full text |Cite|
|
Sign up to set email alerts
|

Remediation of Azure A Dye from Aqueous Solution by Using Surface-Modified Coal Fly Ash Extracted Ferrospheres by Mineral Acids and Toxicity Assessment

Abstract: The Indian coal fly ash (CFA) is composed of 5-15% ferrous fractions. The variation in percentage depends on the source of coal and the operating conditions of the thermal power plants. The present research work reports the recovery of ferrous particles from CFA by the wet magnetic separation method. The morphological, elemental, and chemical properties of the extracted ferrous fractions were analyzed. In order to achieve surface-modified ferrospheres, the extracted ferrospheres were treated with concentrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Site-I was found to be richer than site-II. The reason for this distinction is the soil pollution caused by the deposition of CFA in the soil coming from the STPPs [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. The CFA is stored in the fly ash ponds [ 37 ] near the vicinity of TPPs, from where CFA is released in the form of a slurry mixed with water.…”
Section: Discussionmentioning
confidence: 99%
“…Site-I was found to be richer than site-II. The reason for this distinction is the soil pollution caused by the deposition of CFA in the soil coming from the STPPs [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. The CFA is stored in the fly ash ponds [ 37 ] near the vicinity of TPPs, from where CFA is released in the form of a slurry mixed with water.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the FS were rough-surfaced, with angular and spherule deposits on their surface. The size of the extracted FS varied from 400 to 700 nm (Yadav et al, 2022b). Sharonova et al (2015) reported the extraction of approximately eight fractions of FS from high calcium-containing CFA collected from a Russian TPP.…”
Section: Ferrosphere Properties and Typesmentioning
confidence: 99%
“…Another type of sphere present in CFA is ferrospheres, which are ferrous-rich spherical particles. The size of all these spherical particles varies from 80 nm to several microns (20 µ) depending on the operating conditions of the TPPs (Yadav et al, 2022b). These spherical particles have applications in ceramics, construction, research, and environmental clean-up (Sharonova et al, 2015) and can be separated from CFA by several techniques, most commonly magnetic separation (Shoumkova, 2011;Gupta et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The amount of carbon in coal's constitution determines its qualitative value [12]. Coal might incorporate one or more dangerous elements, such as Arsenic, Beryllium, Boron, Cadmium, Chromium, Cobalt, Lead, Manganese, Mercury, Molybdenum, Selenium, Strontium, Thallium, and Vanadium, in either significant or minute concentrations, based on the origin [13][14][15][16][17][18]. The ignition of pulverized coal in the TPPS results in the production of CFA, a finer powdery material that resembles glass [17].…”
Section: Basic Structural and Chemical Properties Of Cfamentioning
confidence: 99%
“…For instance, Yadav et al, 2020, reported the extraction of ferrospheres from class F CFA, and secondly synthesized iron oxide nanoparticles by chemical and physical routes with high purity (86%-94%) [82]. , also extracted ferrospheres from CFA and performed a surface modification of ferrospheres with acid to make them efficient adsorbents for dye removal from wastewater [18]. Besides this, Sahoo et al, 2016 [83], Goodarzi and Senei, 2009, Valentim et al, 2016, Anshits et al, 2018 [84], and several others have reported the extraction of ferrous fractions from CFA.…”
Section: Cfa In Metallurgymentioning
confidence: 99%